Handbook of cartography - De Lima, Marina (New York Callisto Reference, 2015)
"The space where natural systems and social systems interact is called terrestrial space. Cartography is a means to understand these intricate systems, their interaction and evolution. Hence, cartography has acquired a significant place in the modern scenario. This book provides an overview of the activities which state the significance of cartography in the perception and organization of the territory into distinct areas. Studying the past or understanding the present, cartography has always been a tool to explore all themes of knowledge".
Preface -- Chapter 1 Mathematical analysis in cartography by means of computer algebra system -- Chapter 2 Analysis of pre-geodetic maps in search of construction steps details -- Chapter 3 Web map tile services for spatial data infrastructures : management and optimization -- Chapter 4 Use of terrestrial 3D laser scanner in cartographing and monitoring relief dynamics and habitation space from various historical periods -- Chapter 5 Advanced map optimalization based on eye-tracking -- Chapter 6 GPS positioning of some objectives which are situated at great distances from the roads by means of a "mobile slide monitor - MSM" -- Unexpected 16th century finding to have disappeared just after its printing - Anthony Jenkinson's map of Russia, 1562 -- Chapter 8 Contribution of new sensors to cartography -- Chapter 9 Contribution of SAR radar images for the cartography : case of mangrove and post eruptive regions -- Chapter 10 GIS-based models as tools for environmental issues : applications in the South of Portugal -- Chapter 11 Cartography of landscape dynamics in Central Spain -- Chapter 12 Open source tools, landscape and cartography : studies on the cultural heritage at a territorial scale -- Chapter 13 Imaging the past : cartography and multicultural realities of Croatian borderlands -- Permissions -- List of contributors
Keywords: Cartography; Maps